Cerebral spectroscopic and oxidative stress studies in patients with schizophrenia who have dangerously violently offended - Puri Basant K; Treasaden Ian H (BMC Psychiatry, 2008)
Abstract Background The aim of this study was to bring together all the results of in vivo studies of ethane excretion and cerebral spectroscopy in patients with schizophrenia who have dangerously seriously violently offended in order to determine the extent to which they shed light on the degree to which the membrane phospholipid hypothesis and the actions of free radicals and other reactive species are associated with cerebral pathophysiological mechanisms in this group of patients. Methods The patients investigated were inpatients from a medium secure unit with a DSM-IV-TR diagnosis of schizophrenia. There was no history of alcohol dependency or any other comorbid psychoactive substance misuse disorder. Expert psychiatric opinion, accepted in court, was that all these patients had violently offended directly as a result of schizophrenia prior to admission. These offences consisted of homicide, attempted murder or wounding with intent to cause grievous bodily harm. Excreted ethane was analyzed and quantified by gas chromatography and mass spectrometry (m/z = 30). 31-phosphorus magnetic resonance spectroscopy data were obtained at a magnetic field strength of 1.5 T using an image-selected in vivo spectroscopy sequence (TR = 10 s; 64 signal averages localized on a 70 × 70 × 70 mm3 voxel). Results Compared with age- and sex-matched controls, in the patient group the mean alveolar ethane level was higher (p < 0.0005), the mean cerebral beta-nucleotide triphosphate was lower (p < 0.04) and the mean gamma-nucleotide triphosphate was higher (p < 0.04). There was no significant difference between the two groups in respect of phosphomonoesters, phosphodiesters or broad resonances. Conclusion Our results are not necessarily inconsistent with the membrane phospholipid hypothesis, given that the patients studied suffered predominantly from positive symptoms of schizophrenia. The results suggest that there is increased cerebral mitochondrial oxidative phosphorylation in patients with schizophrenia who have dangerously and seriously violently offended, with an associated increase in oxygen flux and subsequent electron 'leakage' from the electron transport chain leading to the formation of superoxide radicals and other reactive oxygen species. In turn, these reactive species might cause increased lipid peroxidation in neuroglial membranes, thereby accounting for the observation of increased ethane excretion.